Attitude change to secondary health examination using social nudging through a spouse - Wataru Katagiri; Masaaki Shimono; Shunsuke Eguchi; Masaki Takebayashi; Kazuma Iekushi (Environmental and Occupational Health Practice, 2025)
Objectives: Hypertension and dyslipidemia are major risk factors of cardiovascular diseases. Nevertheless, many people do not consider these risk factors important, even if they are noted during their annual health checkups and left untreated for a long time. Here, we report a novel nudge method to encourage people who had these risk factors and examine the resultant changes in the willingness to undergo secondary health examinations. Methods: Employees of Novartis Pharma K.K. and its affiliated companies who had elevated blood pressure and/or lipid levels during annual health checkups were allocated to either the social nudge group (postcards were sent to their spouses) or the control group (postcards were sent to themselves) after confirming their agreement to receive postcards in order to encourage them to take secondary health examination. A web-based survey via email was conducted before and after sending the postcards to understand the willingness to undergo secondary health examinations. Results: Regarding the willingness to undergo the secondary health examinations, a significant difference was observed in the social nudge group (n=58) before (12.1%) and after (46.6%) the postcard was sent (p<0.0001), and no significant difference was observed in the control group (n=9, p=1.0000). The proportion of employees who underwent secondary health examinations did not increase significantly in either group. Conclusions: This study suggested that a social nudge via spouse has a possibility of increasing the willingness to undergo secondary health examinations at low cost. To increase the proportion of undergoing it, combinations with other nudges might be necessary.